PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS MEDIA KARTU KATA BERGAMBAR PADA MATERI SUKU KATA KELAS I - Sarie, Normia; Kartini, Kartini; Bua, Agustinus Toding (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2025)
This research aims to develop a Student Activity Sheet (SAS) based on picture word cards media on syllable material for 1-C grade students at SDN 006 Tarakan. Based on initial observations, it was found that students experienced boredom during the learning process, and many of them were not yet familiar with letters and were not fluent in reading. This is due to the lack of variation in the learning media used. Therefore, this research uses the Research and Development (RD) method with the ADDIE model, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. The research results show that the developing student worksheets has good feasibility based on validation from media experts, material experts, and education practitioners. In addition, students' responses to this developing student worksheets were also positive, indicating that this media is engaging and can enhance students' interest in learning. By using illustrated word cards, it is hoped that students can be more active and engaged in learning, as well as more easily understand syllable material. This research is expected to contribute to the development of innovative and effective learning media, as well as improve the quality of learning in the first grade of elementary school.